An Overview of the Factors that Influence Breastfeeding Mothers in Carrying Out the COVID-19 Vaccine on Working Area At Gladak Pakem Public Health Center Jember Regency - Siti Sulfatus Saniyah; Dini Kurniawati; Iis Rahmawati (Media Keperawatan Indonesia, 2022)
Breastfeeding mothers are included in a vulnerable group that is important to get the COVID-19 vaccine, but some factors influence it carrying out the COVID-19 vaccine. This study aimed to identify the factors that influence breastfeeding mothers in administering the COVID-19 vaccine in the working area of the Gladak Pakem Health Center. The design of this study used a cross-sectional study conducted on 106 breastfeeding mothers with a total sampling technique. Data collection uses 4 questionnaires, namely the respondent's characteristics questionnaire, knowledge about COVID-19 and the COVID-19 vaccine, cues for action, and perceptions of obstacles in carrying out the COVID-19 vaccine. Data collection was carried out door-to-door starting on 23-29 March 2022. The results showed that the majority of breastfeeding mothers had received the COVID-19 vaccine, as many as 88 (83%) breastfeeding mothers. The discussion in this study provides an overview of the dominant factors in breastfeeding mothers who have received the COVID-19 vaccine, including the age factor of the majority who have received the COVID-19 vaccine, namely reproductive age, the religion adopted is Islam, the last education level is high school, employment status the majority do not work, the majority of family support supports, the majority of the disease history has no comorbidities, the level of knowledge of the majority is poor, the majority's cues to act are high. The majority's perception of barriers is low.